Flashforward imagery in speech anxiety: Characteristics and associations with anxiety and avoidance - Thunnissen, Marjolein R.; Nauta, Maaike H.; de Jong, Peter J.; Rijkeboer, Marleen M.; Voncken, Marisol J. (Frontiers in Psychology, 2022)
Speech anxiety (SA) is a highly prevalent social fear. Prospective ‘flashforward’ (FF) imagery of an upcoming social catastrophe may be a particularly important cognitive factor in SA persistence via eliciting anxiety and avoidance behaviors. Since earlier research on imagery and social anxiety has not strictly differentiated between types of negative imagery, the occurrence, precise features, and impact of FF imagery remain unclear. We therefore examined the phenomenological characteristics of FF imagery in SA and mapped the relationship between FF imagery features and anxiety and avoidance. Female participants who approached clinical levels of SA (N = 60) completed questionnaires on SA and avoidance behaviors, and rated anxiety and avoidance in anticipation of an actual speech. FF imagery and emotionally linked autobiographical memories were assessed with semi-structured interviews. All participants reported recurring FF images, which were experienced as vivid, distressing, field perspective images with accompanying negative feelings. Image distress and feelings of threat showed most consistent associations with SA and avoidance measures. Findings add to the conceptualization of SA, and support the clinical relevance of assessing FF imagery. Future experimental studies on FF imagery characteristics are necessary to test the proposed causal impact in SA persistence and to inform additional treatment targets.